2018
DOI: 10.17505/jpor.2018.06
|View full text |Cite
|
Sign up to set email alerts
|

Process-symptom-bridges in psychotherapy: an idiographic network approach

Abstract: Aim: Real-time monitoring of psychotherapeutic processes was recently described as a promising, new way of track-ing periods of change in ongoing treatments. This approach generates complex, multivariate datasets that have to be presented in an intuitive way for clinicians to aid their clinical decision-making. Using network modeling and new approaches in centrality analyses, we examine “bridge nodes” between symptom stress and aspects of the psychotherapeutic process between therapy session (intersession proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
1
15
0
1
Order By: Relevance
“…Only one qualitative study reported that patients with psychosis recognized the advantages of ESM, but did not include clinician views (13). Although patients will be the primary users of ESM, clinicians might be important stakeholders in introducing ESM, and might use ESM themselves to inform treatment decisions (9,14). Therefore, the present study is the first to 1) map the relevance of ESM for psychiatric practice and 2) inquire into barriers and facilitators for implementation through focus groups and interviews with patients and clinicians.…”
mentioning
confidence: 99%
“…Only one qualitative study reported that patients with psychosis recognized the advantages of ESM, but did not include clinician views (13). Although patients will be the primary users of ESM, clinicians might be important stakeholders in introducing ESM, and might use ESM themselves to inform treatment decisions (9,14). Therefore, the present study is the first to 1) map the relevance of ESM for psychiatric practice and 2) inquire into barriers and facilitators for implementation through focus groups and interviews with patients and clinicians.…”
mentioning
confidence: 99%
“…One possibility would also be to integrate alliance-related items into the experience sampling of intersession experiences (e.g., asking about experiences of feeling understood by the therapist, looking forward to future collaboration with the therapist, etc. ), in a similar way to that done by Kaiser and Laireiter (2018).…”
Section: The Working Alliancementioning
confidence: 62%
“…Network models need not be limited to symptoms of psychopathology. Kaiser and Laireiter ( 2018 ) expanded the focus from symptoms of psychopathology by including measures also of patients’ intersession experiences, such as thoughts about past and present sessions, imagined dialogues with the therapist, and positive and negative treatment-related emotions, into the network model. Their results showed a substantial interpersonal variation in how symptom stress interacted with various kinds of such intersession experiences.…”
Section: Insensitivity To Variation and Change In Individual Patientsmentioning
confidence: 99%
“…This is of course not a straightforward question to answer, but it is one that researchers have been addressing from a number of different angles in recent years. Some potentially promising ideas in evidence at WCBCT 2019 included the ever-growing interest in network analysis approaches to the conceptualization, measurement, and modeling of underlying processes or symptoms in psychopathology (e.g., Bringmann et al 2013 ), and a resurgence of interest in idiographic and single case-level approaches (e.g., Fisher and Bosley 2020 ; Kaiser and Laireiter 2018 ). Other developments include using a broader range of trial designs to answer different questions around mechanisms and optimization of multi-component interventions (e.g., Watkins et al 2016 ), adaptive designs that allow addition and replacement of arms in an ongoing trial (e.g., Blackwell et al 2019 ), and designs intended to test sequential allocation to different treatments (e.g., Nelson et al 2018 ).…”
Section: Cbt At the Crossroads: Navigating The Future Pathsmentioning
confidence: 99%